Using of Species-Specific Primers for Molecular Diagnosis of in Vitro Promastigotes of Leishmania donovani - Yaseen , Farah Tariq; Z. Ali, Hayder (Iraqi Journal of Science, 2022)
Visceral Leishmaniasis (VL) is a disseminated protozoan infection caused by Leishmania donovani parasites which affects almost half a million persons annually. Classical diagnosis methods of VL still not very sensitive and time consuming. In this study, we reported the success of polymerase chain reaction (PCR) method to identify L. donovani based on kinetoplast deoxyribonucleic acid (kDNA) for the diagnosis of the parasite using in vitro promastigote cultures. LdI species - specific primer was used to identify L. donovani and the result showed a single band of about ~600bp. It can be recommended that this primer is to be used for detection the visceral L. donovani.